PLATFORM-EMBEDDED ENFORCEMENT IN CRYPTOCURRENCY REGULATION: RETHINKING TAXATION AND ANTI-MONEY LAUNDERING IN INDONESIA’S CROSS-BORDER LEGAL CONTEXT - Muyassar, Asyam Shobir; Fitrijanto, Arief; Nurhidayah, Jessika (PT. Jurnal Center Indonesia Publisher, 2025)
The rapid growth of cryptocurrency transactions presents both opportunities for innovation and risks of cross-border financial crime, including tax evasion and money laundering, which challenge the effectiveness of traditional regulation. This study aims to analyze the effectiveness of platform-based law enforcement particularly the implementation of the Travel Rule, CARF, and KYC in the Indonesian context. The research employs a qualitative multi-site case study method with data triangulation from international literature (FATF, OECD, IMF, Chainalysis, Cambridge) and national regulations (OJK, PPATK, DJP). The findings indicate that cryptocurrency platforms serve as key actors in detection and enforcement; however, their effectiveness is constrained by the sunrise problem, the migration of illicit activities into DeFi and OTC ecosystems, and legal sovereignty tensions arising from the dominance of global platforms. This study introduces the concept of Platform-Embedded Enforcement as a novel theoretical framework, integrating monitoring and enforcement mechanisms directly into platform architectures, thereby enabling compliance to be enforced automatically, in real time, and across jurisdictions. These findings contribute to the development of more adaptive, holistic, and effective cryptocurrency regulation in emerging markets.